10-3x-1=7+3x+2

Simple and best practice solution for 10-3x-1=7+3x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3x-1=7+3x+2 equation:


Simplifying
10 + -3x + -1 = 7 + 3x + 2

Reorder the terms:
10 + -1 + -3x = 7 + 3x + 2

Combine like terms: 10 + -1 = 9
9 + -3x = 7 + 3x + 2

Reorder the terms:
9 + -3x = 7 + 2 + 3x

Combine like terms: 7 + 2 = 9
9 + -3x = 9 + 3x

Add '-9' to each side of the equation.
9 + -9 + -3x = 9 + -9 + 3x

Combine like terms: 9 + -9 = 0
0 + -3x = 9 + -9 + 3x
-3x = 9 + -9 + 3x

Combine like terms: 9 + -9 = 0
-3x = 0 + 3x
-3x = 3x

Solving
-3x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3x + -3x = 3x + -3x

Combine like terms: -3x + -3x = -6x
-6x = 3x + -3x

Combine like terms: 3x + -3x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 1+5(x-8)=2-1(x+5) | | -2=v-6 | | 2x-8=128 | | M=8+3*3 | | 10+4x=46 | | 16=5z-9 | | 9x^2-x+32=0 | | p-65.7=24.81 | | M=8+3*1 | | 1/2+7y=-3 | | 1+2x=2x-5 | | 2+20t-5t^2=0 | | M=8+3*-1 | | 55.00+8.50x= | | 2(4x+4)=-8 | | -d+3=2d | | 6p-6p+18-13-5p= | | 3c+5d=7d-6cford | | Y-5.8=2.3 | | V+2.4=7.95 | | -8x^2-80x-168=0 | | 2745x-1800=45(61x-40) | | V+2.4=7.25 | | 9-6(4u-6)=u+15 | | -289+17y= | | 0.6=Log(2x) | | M=7-3*1 | | k-8=4k+1 | | M=7-3*0 | | -7n+2=-8n-1 | | 125x-275= | | 81=3+3(4k+2) |

Equations solver categories